Incremental Value (Bayesian Framework) of Thoracic Ultrasonography over Thoracic Auscultation for Diagnosis of Bronchopneumonia in Preweaned Dairy Calves. (15th June 2016) - Buczinski, S.; Ménard, J.; Timsit, E.
Abstract : Background: Thoracic ultrasonography (TUS) is a specific and relatively sensitive method to diagnose bronchopneumonia (BP) in dairy calves. Unfortunately, as it requires specific training and equipment, veterinarians typically base their diagnosis on thoracic auscultation (AUSC), which is rapid and easy to perform. Hypothesis/Objectives: We hypothesized that the use of TUS, in addition to AUSC, can significantly increase accuracy of BP diagnosis. Therefore, the objectives were to (i) determine the incremental value of TUS over AUSC for diagnosis of BP in preweaned dairy calves and (ii) assess diagnostic accuracy of AUSC. Animals: Two hundred and nine dairy calves (<1 month of age) were enrolled in this cross‐sectional study. Methods: Prospective cross‐sectional study. All calves from a veal calves unit were examined (independent operators) using the Wisconsin Calf Respiratory Scoring Criteria (CRSC), AUSC, and TUS. A Bayesian latent class approach was used to estimate the incremental value of AUSC over TUS (integrated discrimination improvement [IDI]) and the diagnostic accuracy of AUSC. Results: Abnormal CRSC, AUSC, and TUS were recorded in 3.3, 53.1, and 23.9% of calves, respectively. AUSC was sensitive (72.9%; 95% Bayesian credible interval [BCI]: 50.1–96.4%), but not specific (53.3%; 95% BCI: 43.3–64.0%) to diagnose BP. Compared to AUSC, TUS was more specific (92.9%; 95% BCI: 86.5–97.1%), but had similar sensitivity (76.5%; 95% BCI: 60.2–88.8%). The incremental value of TUS over AUSC was high (IDI = 43.7%; 5% BCI: 22.0–63.0%) significantly improving proportions of sick and healthy calves appropriately classified. Conclusions and Clinical Importance: The use of TUS over AUSC significantly improved accuracy of BP diagnosis in dairy calves.